Memorandum relating to the provision of free medical attendance and medicine to dependants of men serving with the Colours
1914-10-10 1914 1910s 3 pages 2 ARRANGEMENTS FOR THE PROVISION OF FREE MEDICAL ATTENDANCE AND MEDICINE TO DEPENDANTS OF MEN SERVING WITH THE COLOURS. 1. The person requiring medical assistance will apply to the Local Representative Committee either direct or through the Local Branch of the Soldiers' and Sailors' Families Association. In areas where dependants are being dealt with by the Local Branch of the Soldiers' and Sailors' Families Association, applications made to the Branch will be dealt with thereat, the Branch being furnished for the purpose by the Local Representative Committee with a supply of the Medical Book referred to below. Where local circumstances so require, arrangements can be made for Local Branches of the Soldiers' and Sailors' Families Association to apply direct, in the manner indicated in paragraph 17 below, for supplies of the Medical Book. 2. Upon being satisfied that the applicant is dependent upon a man serving with the Colours, the Committee or the Local Branch, as the case may be, will issue a Medical Book, unless they have reason to believe that, in any particular case, the means of the applicant are such that he or she should not receive free medical attendance. It will not be necessary to make the detailed inquiries which are required in the other cases which come before the Committee or Branch, but representations made by doctors or chemists or information in the possession of the Committee will indicate in particular cases that, in view of the means of the applicant, he or she should not receive the benefit of the scheme. Medical Books should not of course be issued to persons entitled to medical benefit under the National Insurance Act. In making arrangements for the issue of Medical Books the Committee will doubtless recognise the necessity for providing special facilities in rural and distant parts of the area. 3. A specimen copy of the Medical Book is enclosed, and a supply is being forwarded to the Local Representative Committee under separate cover. 4. It will be observed that the book is available for the dependant of the soldier or sailor to whom it is issued. In cases of emergency, however, a book may be used to obtain treatment for another member of the family dependent on the particular soldier or sailor, but application should be made as soon as possible in such cases for a separate book for that member. 5. Before issue each book should be completed by the insertion of the requisite particulars on the front page and in instruction 8 on page 3 (see paragraph 10 below). The address of the Local Representative Committee or the Local Branch of the Soldiers' and Sailors' Families Association issuing the book may conveniently be inserted in the space provided on the front page by means of a rubber stamp. 6. The book will be accepted as evidence of bona fides by all doctors and chemists who have offered their services, and must be produced whenever medical attendance or medicine is required. It will be open to doctors or chemists to make representations to the Committee where it would appear that the circumstances of a person applying for treatment or medicine with a Medical Book make it unnecessary for him or her to be admitted to the benefits of the scheme. 7. The patient is instructed to present the book to his or her usual doctor if that doctor's services are available under these arrangements, or, if not, to the nearest available doctor. 8. Any medicine or appliance required will be prescribed by the doctor on one of the prescription forms in the book. The book will be handed back to the patient, and it must then be taken to the patient's usual chemist if his services are available under these arrangements, or, if not, to the nearest available chemist. In rural areas where no chemist is available the medicine and appliances will be supplied by the doctor. The appliances which may be supplied under these arrangements are enumerated on page 4 of the Medical Book. 9. Prescriptions for the medicine or appliances supplied will be detached from the book, retained by the chemist (or doctor), and transmitted by him, not less frequently than once a month, to the Pharmaceutical Society of Great Britain, at 17, Bloomsbury 36/H24/1